1995
DOI: 10.1002/ijc.2910630212
|View full text |Cite
|
Sign up to set email alerts
|

International renal‐cell cancer study. VIII. Role of diuretics, other anti‐hypertensive medications and hypertension

Abstract: Risk of renal-cell cancer in relation to use of diuretics, other anti-hypertensive medications and hypertension was assessed in a multi-center, population-based, case-control study conducted in Australia, Denmark, Germany, Sweden and the United States, using a shared protocol and questionnaire. A total of 1,732 histologically confirmed cases and 2,309 controls, frequency-matched to cases by age and sex, were interviewed. The association between renal-cell cancer and the drugs was estimated by relative risks (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
79
2
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 17 publications
8
79
2
1
Order By: Relevance
“…Only one case of RCC was diagnosed among users of potassium-sparing agents. Based on past studies in this population and others, it is unlikely that calcium antagonists or beta blockers, or ACE inhibitors are associated with cancer (McLaughlin et al, 1995;Olsen et al, 1997;McLaughlin and Lipworth, 2000;Sorensen et al, 2000;Friis et al, 2001;Grossman et al, 2001). To our knowledge this is the first study to examine the relation between angiotensin II antagonists and RCC.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Only one case of RCC was diagnosed among users of potassium-sparing agents. Based on past studies in this population and others, it is unlikely that calcium antagonists or beta blockers, or ACE inhibitors are associated with cancer (McLaughlin et al, 1995;Olsen et al, 1997;McLaughlin and Lipworth, 2000;Sorensen et al, 2000;Friis et al, 2001;Grossman et al, 2001). To our knowledge this is the first study to examine the relation between angiotensin II antagonists and RCC.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, failure to adjust for confounding by pre-existing hypertension in our study may have generated inflated risk estimates. When adjustment for high blood pressure is performed, it appears to eliminate the excess risk associated with diuretic use (McLaughlin et al, 1995). We examined the specific classes of diuretics and found similar risks across all groups.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In men, there was no association with blood pressure. The association of blood pressure with risk of renal cell cancer has been investigated in a number of cohort (Fraser et al, 1990;Grove et al, 1991;Coughlin et al, 1997;Heath et al, 1997;Chow et al, 2000;Choi et al, 2005;Flaherty et al, 2005;Fryzek et al, 2005;Lindgren et al, 2005;Schouten et al, 2005) and case -control (McLaughlin et al, 1995;Yuan et al, 1998;Shapiro et al, 1999) studies, using as principal exposure variable either recorded blood pressure or reported hypertension. In men, recorded blood pressure has shown a convincing exposure -response gradient related to renal cell cancer risk (Coughlin et al, 1997;Chow et al, 2000).…”
mentioning
confidence: 99%